Background subtraction algorithm for moving object detection - Saoud, Ayoub; Mosorov, Volodymyr; Grudzień, Krzysztof (Wydawnictwo Politechniki Łódzkiej, 2016)
Background subtraction technic is a very important part of computer vision applications for successful segmentation of objects from video sequences. In this paper, a segmentation method for moving object using automated moving object detection in a video image sequence based on background subtraction method. Noise is applied to assess the robustness of the algorithm. The background model method and adaptive thresholding is used to compute the foreground object detection mask. A reference frame is initiatly used and considered as background information. Experimental results, which demonstrate the system's performance, are also shown.
Keywords: background subtraction; motion detection; computer vision; odejmowanie tła; detekcja ruchu; wizja komputerowa